Influence of maternal periodontitis on adverse pregnancy outcome: An observational study - Anju Rana; Shiva Manjunath; Hirak Bhattacharya (Wolters Kluwer Medknow Publications, 2022)
Background: Adverse pregnancy outcome is due to deviation from the normal physiological and immunological process. There is conflicting evidence in support of maternal periodontitis as a risk factor for preterm low birth weight (PTLBW). Thus, the aim of the present study is to evaluate the correlation between PTLBW and periodontitis in postpartum mothers based on clinical and microbiological parameters. Materials and Methods: An observational retrospective study was conducted. A total of 103 women with singleton births were included in the study, which was divided into two groups, i.e., Group I-PTLBW and Group II-normal term normal birth weight (NTNBW). Clinical parameters such as oral hygiene index simplified, gingival bleeding index (BOP %), periodontal probing depth (PPD) and and clinical attachment loss (CAL) were recorded on the next day of postpartum. Two samples from each group, i.e., placental extract and the subgingival plaque were collected and transported to the laboratory in an anaerobic medium for microbiological analysis. The statistical analysis was performed using an unpaired t-test and Wilcoxon Mann-Whitney U-test. The P < 0.001 was considered statistically significant. Results: PTLBW group showed significantly higher amounts of periodontal destruction in terms of clinical parameters. The pathogens were also in higher quantities in the PTLBW group compared to the NTNBW group. Conclusion: Periodontitis is related to PTLBW in pregnant women of the studied population. Maternal oral hygiene status delivering PTLBW babies are compromised compared to mothers delivering NTNBW babies. Hence, periodontitis during pregnancy phase is an important health concern for the growing fetus.